Pengaruh Bahan Ajar IPA Terpadu Tema Gelombang Dalam Kehidupan Bermuatan Literasi Era Digital Terhadap Hasil Belajar Siswa Kelas VIII SMP Negeri 8 Padang - Elvida Yulia; Asrizal Asrizal; Ramli Ramli (Universitas Negeri Padang, 2018)
Curriculum 2013 requires science learning in junior high school is implemented in an integrated with the integration in learning. The facts found in integrated IPA learning schools and the integration of literacy in learning are not in accordance with the demands and student learning outcomes are still in the low category. One solution to this problem is the use of integrated IPA teaching the wave theme in a digital literacy-filled life. The purpose of this study is to investigate the effect of the application of integrated IPA Instruction materials wave theme in the life of digital literacy filled with the results of students learning class VIII SMPN 8 Padang.The type of research used is quasi experiment with nonquivalent control group research design with postes only. The study population is all students of class VIII SMPN 8 Padang. The sampling technique used is purposive sampling and random cluster sampling. The sample in this research is keslas VIII B as experimental class and class VIII H as control class. Instrument for knowledge aspect in the form of written test sheet, attitude aspect in the form of observation sheet, and skill aspect in the form of performance appraisal sheet. Research data were analyzed by using descriptive analysis, normality test, homogeneity test, two comparison test average.Based on the results of data analysis can be expressed research results that the use of teaching materials IPA integrated wave theme in the life of literacy digital era gives a meaningful effect on student learning outcomes that include aspects of knowledge, skills aspects and attitude aspects at the level of 95% confidence. From the results of the research data it can be concluded that the teaching materials of IPA integrated wave themes in the life of iterated digital era in an effective scientific approach for use in integrated science learning.